AN ANALYSIS OF GENERIC STRUCTURE OF DESCRIPTIVE TEXT WRITTEN BY STUDENTS AT SMK AL WASHLIYAH 12 SEI RAMPAH - Windy Ananda Putri; Yugi Diraga Prawiyata (PROJECT (Professional Journal of English Education), 2023)
The objective of this study was to determine the generic structure errors in in tenth grade students' efforts to compose descriptive writings at SMK Al Washliyah Sei Rampah. The researcher described and examined data from 20 student-written texts using a qualitative approach. 20 samples were taken from 50 populations. Testing methods are used by researchers to gather data. After reviewing the findings, the researcher came to the conclusion that three students continued to struggle with both identifying descriptive language and understanding how to describe it. Subsequently, Then, 12 students were successful in analyzing the general structure's content and earned 4 points (or 60%), 5 students earned 3 points (or 25%), and 3 students earned 2 points (or 15%). Students make the following mistakes while writing descriptive texts: a) they struggle to distinguish between identification and description; b) They only write descriptive texts containing broad information about a subject rather than to provide details. Students in the tenth grade at SMK Al-Washliyah 12 Sei Rampah exhibit a range of abilities depending on their gender. The data result for the tenth graders at SMK Al-Washliyah 12 Sei Rampah's descriptive writing proficiency is categorized as “excellent.”